Counselling psychology in South Africa. Issue 2 (2nd April 2016) - Bantjes, Jason; Kagee, Ashraf; Young, Charles
Abstract : The origin and development of counselling psychology in South Africa has been profoundly influenced by the country's sociopolitical history and the impact of apartheid. As a result of this, counselling psychologists in the country face a number of challenges and opportunities for the future. In this paper we provide a portrait of counselling psychology in South Africa by describing the current character of the specialty and the context in which South African psychologists work. We critically discuss the challenges that the specialty faces to meet the country's mental health care needs, contest the current Scope of Practice; affirm multiculturalism without essentialising or reifying race and ethnicity, and build an evidence base for community interventions in the country. We also consider how, in the future, counselling psychologists in South Africa may make a more meaningful contribution within public health and the country's health care and education systems.